2011
DOI: 10.1002/smll.201002033
|View full text |Cite
|
Sign up to set email alerts
|

Control of Self‐Assembled 2D Nanostructures by Methylation of Guanine

Abstract: Methylation of DNA nucleobases is an important control mechanism in biology applied, for example, in the regulation of gene expression. The effect of methylation on the intermolecular interactions between guanine molecules is studied through an interplay between scanning tunneling microscopy (STM) and density functional theory with empirical dispersion correction (DFT-D). The present STM and DFT-D results show that methylation of guanine can have subtle effects on the hydrogen-bond strength with a strong depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…The planarity mimicked the adsorption to the gold surfaces and the structure in the crystal. It was shown previously that gold surfaces had little interactions with the adsorbates, which justified our computational approach . Furthermore, the planar symmetry provided a clear σ–π separation, which was useful in our analysis.…”
Section: Computational Detailssupporting
confidence: 62%
“…The planarity mimicked the adsorption to the gold surfaces and the structure in the crystal. It was shown previously that gold surfaces had little interactions with the adsorbates, which justified our computational approach . Furthermore, the planar symmetry provided a clear σ–π separation, which was useful in our analysis.…”
Section: Computational Detailssupporting
confidence: 62%
“…It is known that tiny alteration on the molecular structures may significantly change the intermolecular interactions and consequently subtly tune the supramolecular assembly. In previous work, Bald et al have investigated the effect of methylation on guanine assembly and concluded that a methyl group not only blocks specific H‐bonding sites but also alters the strength of the remaining hydrogen bonds . In our experiment, the substituent alkyl chain has similar effect on the intermolecular interactions of thymine head groups.…”
supporting
confidence: 58%
“…Methylation of NB is an important control mechanism in biology which is applied, for example, in the regulation of gene expression . The effect of methylation on the intermolecular interactions between G molecules was recently studied by Wang and co‐workers . The STM analysis, corroborated by density functional theory (DFT), revealed that the methylation of guanine can have subtle effects on both the pairing nature and the strength of H‐bonds, with a strong dependence on the position of methylation.…”
Section: Self‐assembly In 2dmentioning
confidence: 99%